Proses Pengisian Jabatan dan Upaya Menciptakan Aparatur Pemerintah yang Profesional, Efektif dan Efisien pada Dinas Pendidikan Provinsi Sumatera Barat - susiyanti meilina (Jurnal Administrasi Publik dan Pemerintahan, 2023)
Research has been conducted at the West Sumatra Provincial Education Office on the process of filling positions and efforts to create a professional, effective and efficient government apparatus." The methodology used in this study is qualitative with a descriptive method. namely a form of research that describes and interprets a situation as it is, which is related to how the process of filling positions and efforts to create a professional, effective and efficient government apparatus at the West Sumatra Provincial Education Office. The informant in the study is the person needed to provide information about the problem to be studied. The sources of information in this study are: key informants, early informants or purposively selected key informants. The results of this study revealed the process of filling positions at the West Sumatra Provincial Education Office, and it turned out to be in accordance with the established principles of personnel management, starting from position analysis activities, determining labor sources, the process of accepting workers, selection and appointment, followed by compensation was able to create a professional, efficient and effective government apparatus.